Energy Security Faces Critical Global Attention - Sarjana, Sri (International Journal of Energy Economics and Policy, 2024)
Ensuring a stable and sustainable supply of energy has emerged as a critical global concern in the face of increasing energy demand, environmental degradation and geopolitical uncertainty. As all countries rely heavily on energy to drive economic growth and technological progress, ensuring a stable and accessible supply of energy has become a paramount imperative. This study aims to explore the multifaceted concept of energy security and its derivative topics for follow-up development in the future. The research approach combines bibliometric analysis and the analytical hierarchy process which was developed to analyze the derivatives of the concept of energy security. Data sourced from scientific literature collected from journal publications published from 2018-2022. The results of the study found three priority topics that have the potential to have novelty in the development of energy security in the future, including clean energy, energy harvesting and energy equity. This priority topic underscores the importance of a transition towards sustainable energy system that not only guarantees a reliable supply of energy but also promotes environmental stewardship and people’s well-being.